The epidemiology and economic consequences of pain - Henschke, Nicholas; Kamper, Steven J.; Maher, Chris G. (Mayo Clinic proceedings, 2015)
Pain is considered a major clinical, social, and economic problem in communities around the world. In this review, we describe the incidence, prevalence, and economic burden of pain conditions in children, adolescents, and adults based on an electronic search of the MEDLINE and EMBASE databases for articles published from January 1, 2000, through August 1, 2014, using the keywords pain, epidemiology, burden, prevalence, and incidence. The impact of pain on individuals and potential risk factors are also discussed. Differences in the methodology and conduct of epidemiological studies make it difficult to provide precise estimates of prevalence and incidence; however, the burden of pain is unquestionably large. Improved concepts and methods are needed in order to study pain from a population perspective and further the development of pain prevention and management strategies.
Gesehen am 24.08.2020